PRELIMINARY RESULTS OF DELAYED PRIMARY BLADDER EXSTROPHY RECONSTRUCTION IN FEMALE PATIENT: A CASE REPORT - Setiawan, Ilham Rachmat; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2024)
Objective: Reporting a rare case and provide a view of bladder extrophy management. Case(s) Presentation: A 12-year-old female complained of an open abdominal wall below the umbilicus accompanied by continuous incontinence of urine since birth. The MRI showed diastasis symphisis 5.1 cm and a soft tissue defect in the suprapubic region, suspicious of bladder exstrophy. Bladder mucose biopsy showed squamous metaplasia. The patient underwent pelvic osteotomy, bladder wall closure, bladder neck reconstruction, abdominal closure with double keystone flap with proceed mesh, and external fixation. A cystostomy catheter was placed until one week after surgery, and the patient was able to hold the urge to urinate and started to move around while sitting. Two months after the reconstruction, the primary closure and keystone removal on skin defect were carried. The patient was already able to walk and continence the urine. Discussion: Bladder extrophy is a rare condition. Currently delayed reconstruction on bladder growth is the subject of debate and speculation. The patient’s condition in this presented case improved, this is in accordance with the literature that states that delayed reconstruction can still be considered in special conditions that do not allow early reconstruction. Conclusion: Delayed bladder reconstruction and bladder neck reconstruction can improve the anatomy of the bladder and quality of life on certain cases. Keywords: Bladder exstrophy, bladder reconstruction, female bladder exstrophy.